2011
DOI: 10.1103/physreve.84.046608
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of spherical capsules

Abstract: We investigate buckling of soft elastic capsules under negative pressure or for reduced capsule volume. Based on nonlinear shell theory and the assumption of a hyperelastic capsule membrane, shape equations for axisymmetric and initially spherical capsules are derived and solved numerically. A rich bifurcation behavior is found, which is presented in terms of bifurcation diagrams. The energetically preferred stable configuration is deduced from a least-energy principle both for prescribed volume and prescribed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
245
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(261 citation statements)
references
References 28 publications
15
245
0
1
Order By: Relevance
“…The mechanism of buckling in axisymmetric conformations was quite recently investigated in detail by Knoche et al [12], with the study of various metastability branches. At first significative order, their calculations show that for the trivial isotropic ("spherical") deformation, the relative volume variation due to an external overpressure ∆P = P ext − P int expresses:…”
Section: Buckling Volumementioning
confidence: 99%
See 3 more Smart Citations
“…The mechanism of buckling in axisymmetric conformations was quite recently investigated in detail by Knoche et al [12], with the study of various metastability branches. At first significative order, their calculations show that for the trivial isotropic ("spherical") deformation, the relative volume variation due to an external overpressure ∆P = P ext − P int expresses:…”
Section: Buckling Volumementioning
confidence: 99%
“…A few months ago, stability analysis allowed a detailed study of buckling toward axisymmetric conformations [12]. Experimental [13,3,14,15,16,1,17] and numerical [3,18,17] deflation studies showed shapes holding several dimples, also called "multiple indentation".…”
Section: Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, nonlinear shell theory has been used to investigate the postbuckling behaviour [13], which revealed that the buckled shape is unstable with respect to further volume reduction if the pressure is controlled. Numerical analyses of nonlinear shape equations have been used to obtain bifurcation diagrams for the axisymmetric deformation behaviour [14,15]. In this paper, we will approach this classical axisymmetric buckling using two different models for axisymmetric deformations.…”
Section: Introductionmentioning
confidence: 99%